Industrial training report: Perbadanan Perpustakaan Awam Johor / Norafiqah Parman - Parman, Norafiqah (Universiti Teknologi MARA, Negeri Sembilan, 2019)
This industrial training report have 4 chapters which is chapter 1 is introduction, chapter 2 is organization information, chapter 3 1s industrial training activities and chapter 4 is industrial training reflection. Chapter consists of the background of organization, organization structure of the library, library services and collection. Chapter 2 consists of departmental structure and departmental function while chapter 3 consists of training activities and special project and the last chapter is chapter 4 consists of conclusion of the report. The trainee need to complete the study by doing industrial training for 5 months starting from 1 August 201 9 until 3 1 December 2019. Perbadanan Perpustakaan Awam Johor is a public library that selected by the trainee to do internship training. There are 5 departments in the library which is administrative unit, finance unit, 'Galakan Membaca' unit, technical management unit and service reference and information unit. The trainee schedule was prepared by an assistant librarian which is Mr. Afzan bin Mohamed. While undergoing the industrial training, the trainee learn to improve self-confidence level, be more punctual and manage time effectively. Last but not least, the knowledge, skills and experienced gained by the trainee is a big opportunity to help the trainee in getting job in future and also be a good librarian in future.